Análise sociolinguística da manutenção da língua pomerana em Santa Maria de Jetibá, Espírito Santo - Bremenkamp, Elizana Schaffel (2014)
This dissertation investigates the process of maintaining the Pomeranian language in the municipality of Santa Maria de Jetibá, Espírito Santo, considered the most Pomeranian in the State ( PMSMJ , 2013 ) . First of all, the history of immigration is registered. Then it brings a sociolinguistic characterization of “santa-mariense” Pomeranian community. To do so, it is shown the linguistic repertoire of the community in study; discusses the attitudes and loyalty of the group in relation to the Pomeranian and Portuguese in order to check their status towards speakers; the domination and social functions performed by the official languages and immigration are addressed; there is a Pomeranian/Portuguese bilingualism in order to understand whether if it is stable or it aims the subtraction of the minority language; it means the formation of social networks; and discusses the ethnic identity of Pomeranians. Finally, we analyze the maintenance of Pomeranian for 150 years in an attempt to elucidate the factors maintaining and clarifying its degree of vitality. This study belongs to the sociolinguistics field, specifically in studies of Language Contact. Therefore, it approaches a wide range, but complementary to sociolinguistic themes and also of theoretical constructs of anthropology, which are identity, ethnicity and social networks. According to the sociolinguistic tradition, the languages of immigration are usually doomed to extinction in the third generation descendants of immigrants - the Third Generation Law; but although rare, there are exceptions. There are numerous factors that influence the processes of language maintenance/replacement and then it derives its complexity: the same factors, in the same directionality, it may favor both incidents. Thus, each case must be taken into consideration and be studied in the context of the society in which it operates. Besides all the bibliographic apparatus, this study makes use of qualitative approach, which allows a more revealing analysis of interviews with Pomeranians descendants and of the Participants Observation. The results, demonstrated through charts, statistical tables and interpretative analysis of excerpts from interviews shows that the Pomeranian community "santa-mariense" is bilingual in 85%. Interviewed people over 55 years old, have receptive skills in Portuguese, and their competence in this language does not reach 2% . Although, the youngers are more receptive and have productive skills in Portuguese, that reach 100%, and in Pomeranian 72.7% . Women and those with more than 8 years of scholarity are closest to the official language. However, the community shows highly supportive of bilingualism. The second group, between 14-30 years old, reflects the worst rates in relation to the Pomeranian language. This is because its an unstable group and quite emotionally affected by the language prejudice, as well as the linguistic market. Regarding the domains and social functions, the analyzes indicate a high degree of bilingualism in almost all functions and scope This high level of bilingualism occurs, since this community is early simultaneous bilingual balanced . Given these results, we show that the present moment requires attention and care for the transfer of the Pomeranian language within the family. However, no evidence of an imminent replacement process were found.